Using SenseMaker® to Understand the Prioritization of Self-Care and Mental Health of Minoritized Engineering Students during the 2020 Global Pandemic - Racheida S. Lewis; Trina Fletcher; Animesh Paul; Diane Abdullah; Zaniyah V. Sealey (MDPI AG, 2023)
The 2020 global pandemic caused by COVID-19 forced higher education institutions to immediately stop face-to-face teaching and transition to virtual instruction. This transition has been difficult for engineering education, which has strong hardware, software, and practical/laboratory components, and has further exacerbated the personal and professional experiences of minoritized students in engineering. This study sought to answer the following overarching research question: How has the abrupt transition to online instruction due to COVID-19 affected students traditionally underrepresented in engineering? The abrupt transition for minoritized students and their decision to prioritize their mental health was further explored to answer the following: (1) How many minoritized students chose to prioritize their mental health? (2) How do minoritized students describe their experiences and choices to prioritize (or not) their mental health? Using SenseMaker, participants shared stories using the following prompt: Imagine you are chatting with a friend or family member about the evolving COVID-19 crisis. Tell them about something you have experienced recently as an engineering student. After completing their narrative, a series of triadic, dyadic, and sentiment-based multiple-choice questions were presented. Student responses varied, including positive experiences, which resulted in a strong prioritization, while others had negative experiences resulting in varied prioritizations. Some students chose to prioritize their mental health to remain mentally and emotionally healthy; some with negative experiences abandoned self-care strategies in order to tend to the needs of academics and family. Participants' decisions to prioritize their mental health were not monolithic.